Perbandingan Pengaruh Atribut Iklan Viral yang Dipilih Terhadap Belanja Perilaku Generasi Milenial - Studi Empiris - Megra Maulana; Nanang Wahyudin (Economics and Digital Business Review, 2024)
This study aims to evaluate how specific viral advertising elements affect Millennial consumers' purchasing decisions. We completed these two stages to reach our goal: The authors' initial step involved figuring out how the chosen features affected consumers' overall buying habits. Additionally, in the second phase, the effects of two research initiatives will be compared: ABSOLUT's viral campaign and 4KA's guerilla efforts. 360 respondents filled out a questionnaire about a sample of young clients, which provided the data for the analysis. The collaborative and cooperative millennial generation (1975-2000) Technology should only be used for passionate values and adventurous activities. The eight characteristics listed in the survey section of the questionnaire were innovation, relevance, aesthetics, clarity, comedy